In Vitro Efficacy of Targeted Fermentable Oligosaccharides, Disaccharides, Monosaccharides, and Polyols Enzymatic Digestion in a High-Fidelity Simulated Gastrointestinal Environment - Kenny Castro Ochoa; Shalaka Samant; Anjie Liu; Cindy Duysburgh; Massimo Marzorati; Prashant Singh; David Hachuel; William Chey; Thomas Wallach (Gastro Hep Advances, 2023)
Background and Aims: Irritable bowel syndrome (IBS) is characterized by abdominal pain and changes in bowel habits. Fermentable oligosaccharides, disaccharides, monosaccharides, and polyols (FODMAPs) are poorly absorbed short-chain carbohydrates that may drive commensal microbial gas production, promoting abdominal pain in IBS. Low-FODMAP diet can result in symptomatic improvement in 50%–80% of IBS patients. However, this diet is not meant to be sustained long term, with concern for downstream nutrition and microbial issues. In this study, we evaluate the function of a targeted FODMAP enzymatic digestion food supplement FODMAP enzymatic digestion (FODZYME) containing a fructan-hydrolase enzyme (with significant inulinase activity) in a simulated gastrointestinal environment. Methods: Using SHIME (Simulator of the Human Intestinal Microbial Ecosystem), a multi-compartment simulator of the human gut, FODZYME dose finding assay in modeled gastrointestinal conditions assessed enzymatic ability to hydrolyze 3 g of inulin. Full intestinal modeling assessing digestion of inulin, absorption of fructose, gas production, and other measures of commensal microbial behavior was completed using 1.125 g of FODZYME. Results: After 30 minutes, 90% of the inulin was converted to fructose by 1.125 g of FODZYME. Doubling dosage showed no significant improvement in conversion, whereas a half dose decreased performance to 77.2%. Seventy percent of released fructose was absorbed during simulated small intestinal transit, with a corresponding decrease in microbial gas production, and a small decrease in butyrate and short-chain fatty acid production. Conclusion: FODZYME specifically breaks down inulin in representative gastrointestinal conditions, resulting in decreased gas production while substantially preserving short-chain fatty acid and butyrate production in the model colon. Our results suggest dietary supplementation with FODZYME would decrease intestinal FODMAP burden and gas production.